PSYCHOPATHOLOGICAL SYMPTOMS AND MALADAPTIVE SCHEMES IN ADULT USERS OF A PSYCHOLOGICAL CARE CENTER IN THE CITY OF POZA RICA - García, Celina Márquez (Journal of Posthumanism, 2024)
This article investigates the prevalence of clinical symptoms and maladaptive schemas in low-income adults who attend a psychological center. Research reveals that the most common symptoms include phobias, somatization, obsessions and depression, with clear differences between men and women in terms of maladaptive schemes. In women, self-sacrifice and abandonment prevail, while in men distrust and entitlement stand out. These results underscore the importance of a comprehensive approach to address both clinical symptoms and maladaptive beliefs, considering factors of gender and socioeconomic context.